Blockchain-based and verifiable multidimensional data aggregation and sharing scheme for smart grid - Jianwei CHEN; Shuyu WANG; Meiping ZHANG; Zhenping ZHANG (Tongxin xuebao)
Aiming at the problem that how to support lightweight multi-dimensional data aggregation, achieve double-end integrity verification of multi-dimensional data in the overall process of the system, and deal with the centralization of cloud servers, a blockchain-based and verifiable multidimensional data aggregation and sharing scheme for smart grid was proposed.Firstly, in order to meet the demand for fine-grained analysis of power data in smart grid, privacy-preserving multidimensional data aggregation was achieved by using masked values and Horner’s rule.On this basis, for the data integrity verification problem of the existing data aggregation scheme in the sharing of cloud storage data with the third party, a new signature algorithm was designed by borrowing the RSA-based multiplicative homomorphic commitment scheme and homomorphic hash function homomorphism, which enabled the cloud server to verify the integrity of aggregated data and be used for integrity verification in the data sharing phase, i.e., it achieved double-end verifiability of cloud storage data and was resistant to internal attacks.Meanwhile, an aggregated data sharing architecture based on federated chain multichain was proposed to effectively avoid centralisation problems such as single-machine processing bottleneck and vulnerability to attacks.The theoretical analysis proves the security of the scheme.Performance experiments show that the proposed scheme has lower computation and communication costs compared with existing schemes.